Latest Concepts in Endodontic Management of Pregnant Patients - Maryam Kuzekanani (Hindawi Limited, 2023)
Pregnant patients and how to manage their treatments is one of the most important challenges in endodontic practice. Endodontic treatment on pregnant women is sometimes an emergency condition to control toothache due to irreversible pulpitis and odontogenic infection. Tooth decay, oral health, local and general anesthesia, analgesics, antibiotic prescription, drug interactions, and X-ray radiation are the most important considerations that may impact treatment planning and endodontic practice in pregnancy. The aim of this article is to notify and explain the latest concepts in the endodontic management of pregnant patients.